Anti-Müllerian hormone as a diagnostic marker for testicular degeneration in dogs: insights from cryptorchid models - Posastiuc, Florin Petrișor; Rizzoto, Guilherme; Constantin, Nicolae Tiberiu; Nicolae, George; Chiers, Koen; Diaconescu, Alexandru Ilie; Șerban, Andreea Iren; Van Soom, Ann; Codreanu, Mario Darius (Frontiers in Veterinary Science, 2024)
IntroductionThe increasing prevalence of infertility in male dogs in clinical practice mirrors current trends seen in human medicine. Acquired infertility is notably more common in dogs compared to congenital causes, with conditions such as testicular degeneration leading to irreversible loss of fertility. Current diagnostic methods for testicular degeneration, such as histopathological and cytological examinations, rely on testicular biopsy or fine needle aspiration, making them less feasible for routine use. Anti-Müllerian hormone (AMH), produced by Sertoli cells, has emerged as a potential alternative biomarker for testicular health, which can be measured in serum. This study evaluates AMH as a potential marker for testicular degeneration, using cryptorchid dogs as models for impaired fertility and altered testicular histology.MethodsThe relationship between serum AMH levels and AMH tissue expression with impaired spermatogenesis and altered histology was investigated. Serum AMH levels were determined in intact, cryptorchid, and castrated individuals using an immuno-enzymatic ELISA kit and compared between subgroups based on testicular location. Tissue AMH immuno-expression was differentially quantified in two regions of interest (ROIs), the interstitial space and the seminiferous tubule, in both descended and retained gonads. Furthermore, testicles were analyzed using histomorphometric analysis in seminiferous tubules, while spermatogenesis was evaluated using the Johnsen score.ResultsSerum AMH levels were positively correlated with AMH expression assessed in both interstitial space (ρ = 0.494, p ≤ 0.01) and seminiferous tubules (ρ = 0.610, p ≤ 0.001). Conversely, serum AMH levels showed a negative correlation with the seminiferous tubule area (ρ = −0.435, p ≤ 0.05). Smaller seminiferous tubule areas were linked to increased AMH reactivity in both seminiferous tubules (ρ = −0.774, p ≤ 0.001) and interstitial space (ρ = −0.725, p ≤ 0.001). Additionally, lower Johnsen scores were associated with higher serum AMH levels (ρ = −0.537, p ≤ 0.01) and elevated AMH expression in both seminiferous tubules (ρ = −0.756, p ≤ 0.001) and interstitial space (ρ = −0.679, p ≤ 0.001).DiscussionOur results suggest that higher serum levels and tissue expression of AMH are linked to smaller seminiferous tubules and poorer Johnsen scores, reflecting degenerative changes and Sertoli cell dysfunction in retained testicles. Given the similarities in the mechanisms that increase AMH levels in both cryptorchid and non-cryptorchid testicles affected by testicular degeneration, this study recommends using AMH as a marker for diagnosing testicular degeneration in dogs.